2018
DOI: 10.1093/brain/awy229
|View full text |Cite
|
Sign up to set email alerts
|

White matter diffusion alterations precede symptom onset in autosomal dominant Alzheimer’s disease

Abstract: See Jacobs and Buckley (doi:) for a scientific commentary on this article.Despite the prevalence of white matter alterations in Alzheimer's disease, their occurrence in the presymptomatic phase is poorly understood. Araque-Caballero et al. report that diffusivity alterations occur first within the anterior and posterior callosal fibres approximately 10 years before the onset of dementia symptoms in autosomal dominant Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
131
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 110 publications
(158 reference statements)
10
131
0
2
Order By: Relevance
“…13 In autosomal dominant AD, we previously reported higher MD within the forceps major 10 years before symptom onset, with other major long-projecting fibers tracts such as the inferior frontooccipital fasciculus, superior longitudinal fasciculus, and forceps minor affected subsequently. 13 Similarly, in the current study, we observed significant amyloid-related MD increase that was located primarily in temporal and posterior brain regions. It should be noted that the white matter alterations extended to frontal fiber tracts such as the anterior thalamic radiation.…”
Section: Discussionmentioning
confidence: 84%
“…13 In autosomal dominant AD, we previously reported higher MD within the forceps major 10 years before symptom onset, with other major long-projecting fibers tracts such as the inferior frontooccipital fasciculus, superior longitudinal fasciculus, and forceps minor affected subsequently. 13 Similarly, in the current study, we observed significant amyloid-related MD increase that was located primarily in temporal and posterior brain regions. It should be noted that the white matter alterations extended to frontal fiber tracts such as the anterior thalamic radiation.…”
Section: Discussionmentioning
confidence: 84%
“…Such improved specificity may be due to neuroaxonal degradation occurring secondary to neuronal death during the onset and progression of AD‐related cortical atrophy. Furthermore, emerging evidence leveraging CSF Aβ42 and hyperphosphorylated tau have linked these core AD pathologies to white matter microstructural damage among aging adults [5] even in familial AD [27,28]. These findings suggest damage to the cerebral white matter (and underlying axons) may be more directly involved in the AD pathological cascade than previously recognized.…”
Section: Discussionmentioning
confidence: 94%
“…3A,B). Thus suggesting that a marked degree of hypoperfusion-ischemia that may remain however below the T2-weighted MRI detectability and does not lead to strokes, may trigger APP misfolding and may explain the link between brain microstructural changes detected on diffusion tensor imaging (DTI) and likely hypoxic-ischemic hyperintensities in white matter, detected decades before the onset of symptomps and autosomal dominant AD cases 66,67 as well as common late-onset sporadic cases and elderly people 68 .…”
Section: Discussionmentioning
confidence: 99%